EFFECTS OF SOAKING TIME INTERVALS OF HEAVY METALS IN OYSTER IN A CONTAMINATED ZONE IN RIVERS STATE - OKEREKE, A.N; EZEAFULUKWE, C.F (Nigerian Journal of Fisheries, 2018)
The study was conducted to evaluate the efficacy of different soaking time interval at both seasons in the removal of some heavy metals (Lead, Chromium, Cadium, Iron, Zinc and Potassium) in Oyster. The result showed that time was significantly different (p< 0.05) for Cd, and was insignificant for Pb, Cr, Fe, Zn and K (p > 0.05) for rainy seasons. There was a significant difference on 24h soaking while between 46 hours and 96 hours no significant differences was observed during rainy season. In the dry season , result shows that time was significantly different (p< 0.05) for Pb, Cr and Cd, but time was insignificant for Fe, Zn and K (p > 0.05). The reduction during rainy season was higher than the reduction in dry season. The concentration of Pb, Cr, Cd increased in dry season at different intervals of soaking while Fe, Zn and K reduced slightly. This slow reduction of these heavy metals (Cr, Cd and Pb) through soaking might be as a result of rate of contamination in this creek and the nature of this metals in the atomic circle. .The soaking process did not bring about satisfactory results in the reduction of the heavy metals.